A model based on feature objects aided strategy to evaluate the methane generation from food waste by anaerobic digestion. (February 2018) - Yu, Meijuan; Zhao, Mingxing; Huang, Zhenxing; Xi, Kezhong; Shi, Wansheng; Ruan, Wenquan
Highlights: FOs aided strategy was used to investigate food waste anaerobic digestion. The kinetics of FOs and food waste were determined by kinetic models. A model based on FOs was established to analyze the methane generation process. Abstract: A model based on feature objects (FOs) aided strategy was used to evaluate the methane generation from food waste by anaerobic digestion. The kinetics of feature objects was tested by the modified Gompertz model and the first-order kinetic model, and the first-order kinetic hydrolysis constants were used to estimate the reaction rate of homemade and actual food waste. The results showed that the methane yields of four feature objects were significantly different. The anaerobic digestion of homemade food waste and actual food waste had various methane yields and kinetic constants due to the different contents of FOs in food waste. Combining the kinetic equations with the multiple linear regression equation could well express the methane yield of food waste, as the R 2 of food waste was more than 0.9. The predictive methane yields of the two actual food waste were 528.22 mL g −1 TS and 545.29 mL g −1 TS with the model, while the experimental values were 527.47 mL g −1 TS and 522.1 mL g −1 TS, respectively. The relative error between the experimental cumulative methane yields and the predicted cumulative methane yields were both less than 5%.